Chemical compositions of garnet and clinopyroxene and their genetic significances in Yemaquan skarn iron–copper–zinc deposit, Qimantagh, eastern Kunlun - Zuo, Pengfei; Liu, Xuefei; Hao, Jinhua; Wang, Yashuai; Zhao, Rui; Ge, Songsheng (Journal of geochemical exploration, 2015)
The Yemaquan skarn deposit in the northwestern part of the Qimantagh is located in the eastern Kunlun orogenic belt. The deposit is hosted in carbonate rocks, siltstones, and sandstones of the Cambrian–Ordovician Tanjianshan Group and Late Carboniferous Di'aosu Formation. These rocks are intruded by Triassic calc-alkaline granitoid that extended NW–SE. Three stages of mineralization have been identified, i.e., pre-ore stage, syn-ore stage, and post-ore stage. The prograde skarn stage, which corresponds to the pre-ore stage, is dominated by clinopyroxene and garnet. Clinopyroxene is much more abundant than garnet in the deposit and consists of three types of clinopyroxene in the deposit. In terms of the end-members diopside (CaMgSi2O6), hedenbergite (CaFeSi2O6), and johannsenite (CaMnSi2O6), namely, type I (with an average composition of Di92Hd7Joh1), type II (with an average of composition of Di62Hd36Joh2), and type III (with an average composition of Di24Hd54Joh22) occurred from the proximal intrusions to the distal wall rocks. Type I, II, and III clinopyroxenes are associated with copper–iron, iron, and zinc–lead mineralization, respectively. Garnet mostly occurred in the middle of exoskarn zonations and is associated with type II clinopyroxene. The distribution of the garnet in the skarn zonation could be explained by the stability fields of clinopyroxene, which is strongly dependent on composition. Based on mineral assemblages, the formation of type II and type III, comparative to type I clinopyroxene, is in more reduced condition in the distal skarn. Moreover sulfur isotope carried out on sulfide minerals from both the prograde and retrograde stages show a variable and wide range of δ34S values (−6.9 to 4.2‰ δ34S), suggesting that the skarn-forming fluid may have been affected by the reduced wall rocks. The low garnet/clinopyroxene ratios observed at the deposit might be caused by the clinopyroxene composition variations and reduced wall rocks. •An increase in Fe and Mn and a decrease in Mg in clinopyroxene along skarn zonation•The mineralization sequence Cu–Fe→Fe→Zn–Pb is associated with the clinopyroxenes.•Formation of type I and II clinopyroxenes is in more reducing conditions than type I.•Wall rocks and clinopyroxene compositions affect the garnet/clinopyroxene ratios.